Blugold Seminar Research Project : Effective First Year College Writing Experience - Bultman, Alie; Bunce, Nicole; Moua, Katherine; Hall, Jim (My University, 2013)
The purpose of this study was to investigate best practices and strategies in order to support the implementation of the new Blugold Seminar.
Color poster with text and images.
Keywords: Blugold Seminar--Wisconsin--Eau Claire; Composition (Language arts)--Study and teaching (Higher); University of Wisconsin--Eau Claire; Posters; First-year English